Species of Macrostomum (Macrostomorpha: Macrostomidae) from the coastal region of Lima, Peru, with comments on M. rostratum Papi, 1951 - Reyes, Jhoe; Brusa, Francisco (Zootaxa, 2017)
Species of Macrostomum are present in almost all regions of the world. These flatworms occur in different kinds of environments, from freshwater to marine ecosystems. Although Peru is considered one of the megadiverse countries in South America, little is known about freshwater microturbellarians in this country. Here we report the presence of M. rostratum Papi, 1951 for the first time in Peru, in a coastal brackish water wetland, and that of M. quiritium Beklemischev, 1951 and M. tuba Graff, 1882 in an inland portion of a river near the city of Lima. All the species were studied alive. Comments on the habitat and associated fauna are given. Detailed information on the copulatory system is provided for M. rostratum; the male system has a bilobed seminal vesicle with thick walls and full of spindle-shaped sperm cells, and a stylet in the form of a solid curved inverted cone with a subterminal opening located on the concave side of the stylet. These findings led us to suggest that M. rostratum may exhibit a hypodermic mating syndrome. The three species of Macrostomum reported here are widespread and, although the diagnostic characters of the species are present, some morphological differences in the copulatory stylet suggest they are cryptic species.